2014
DOI: 10.1177/1934578x1400900529
|View full text |Cite
|
Sign up to set email alerts
|

Hedyotis diffusa Water Extract Diminished the Cytotoxic Effects of Chemotherapy Drugs against Human Breast Cancer MCF7 Cells

Abstract: Hedyotis diffusa is a Chinese herbal medicine widely used in combination with other herbal medicines such as Scutellaria barbata to treat various types of cancer. Late-stage and recurrent cancer patients usually use H. diffusa during chemotherapy in expecting to achieve additive or synergistic therapeutic effects. Several classes of active ingredients, including anthraquinones, iridoid glucosides and stigmasterols, have been isolated and characterized from H. diffusa. In the current study, we isolated alkaloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…HDW has long been extensively utilized in several Chinese medicine formulae to clinically treat inflammatory and infectious diseases like sore throat, bronchitis, hepatitis, urethritis, and appendicitis [ 16 – 20 ]. Moreover, HDW has also been used as an adjuvant therapy for the treatment of certain malignancies, including colorectal, liver, stomach, lung, and breast cancers, with relatively fewer and milder side effects [ 18 , 21 30 ]. It has been reported that HDW displays an array of pharmacological effects, including antioxidant, anti-inflammatory, antibacterial, antiangiogenic, proapoptotic, and immunomodulatory activities [ 14 , 31 – 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…HDW has long been extensively utilized in several Chinese medicine formulae to clinically treat inflammatory and infectious diseases like sore throat, bronchitis, hepatitis, urethritis, and appendicitis [ 16 – 20 ]. Moreover, HDW has also been used as an adjuvant therapy for the treatment of certain malignancies, including colorectal, liver, stomach, lung, and breast cancers, with relatively fewer and milder side effects [ 18 , 21 30 ]. It has been reported that HDW displays an array of pharmacological effects, including antioxidant, anti-inflammatory, antibacterial, antiangiogenic, proapoptotic, and immunomodulatory activities [ 14 , 31 – 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hedyotis diffusa Willd is a commonly used Chinese herbal medicine with various pharmacological activities such as anti-tumor, anti-inflammatory, antioxidant and immunomodulatory ( Dong et al, 2014 ) ( Chen et al, 2016b ) ( Gao et al, 2016 ) ( Kuo et al, 2015a ). It has been used to treat various diseases for thousands of years ( Meng et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The total flavonoids of Hedyotis diffusa (FOD) are the main active components of Hedyotis diffusa Willd , most of which are the derivatives of flavonol aglycone of kaempferol and quercetin ( Chen et al, 2016a ; Qian et al, 2021 ). FOD were found to have antitumor activity ( Lee et al, 2011 ; Dong et al, 2014 ; Zhang et al, 2016 ). Previous studies have shown that the FOD is widely used to treat cancers of various types, including breast cancer ( Ma et al, 2020 ), lung adenocarcinoma, lung cancer ( Su et al, 2019 ; Huang et al, 2022 ), Prostate Cancer ( Song et al, 2019a ), Cervical Cancer ( Qian et al, 2021 ) and HCC ( Chen et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies reported the variety of pharmacological effects of BHSSC, including its anticancer, antioxidative, neuroprotective, and immunomodulating activities (49)(50)(51)(52). This variety in the effects of BHSSC may be because different components of BHSSC have different effects.…”
Section: Discussionmentioning
confidence: 99%